High-conductivity proton exchange membrane and preparation method thereof
By adding free radical inhibitors to the preparation process of the proton exchange membrane, the acid absorption rate and hydrophilic phase region continuity of the membrane are improved, and the problem of difficult to balance the proton conductivity and chemical stability in the prior art is solved, and a high conductivity proton exchange membrane preparation is achieved, with simple process and low cost.
Patent Information
- Application Number
- CN202510387153.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-31
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-03-31
AI Technical Summary
It is difficult to balance the proton conductivity and chemical stability of existing proton exchange membrane fuel cells, and the preparation process requirements are high and the cost is high.
By adding different types of free radical inhibitors during the preparation of the proton exchange membrane, the acid absorption rate and hydrophilic phase region continuity of the membrane are improved, thereby improving the conductivity. The specific method includes mixing the polymer material with an organic solvent, adding quaternization reagent and free radical inhibitor after ultrasonic reaction, and finally baking the film in an oven to complete the preparation of the film.
The effect of improving the conductivity of the proton exchange membrane is achieved, and the preparation process is simplified, the requirements for the instrument are reduced, the reaction time is short, and the free radical inhibitors used are cheap and rich in types, which can effectively improve the conductivity of the proton exchange membrane.
Smart Images

Figure CN119905622A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of membrane preparation, and more specifically, to a high-conductivity proton exchange membrane and a preparation method thereof. Background Art
[0002] Proton exchange membrane fuel cells have the advantages of no pollution, high energy conversion efficiency, fast startup speed, simple structure, and convenient operation and maintenance. They are new energy devices that have attracted much attention in recent years. Proton exchange membrane is a key component of proton exchange membrane fuel cells, which has a significant impact on the actual performance of the battery during operation.
[0003] At present, the research direction of proton exchange membranes is mainly to balance the proton conductivity and chemical stability, the permeability of active substances such as fuels, etc., which can be achieved mainly through structural modification, blending modification, surface modification and hybridization / composite modification of proton conductive polymer molecules and introduction of functional dopants. Proton conductivity is one of the most critical properties of proton exchange membranes. Improving the proton conductivity of proton exchange membranes can effectively improve the performance of proton exchange membrane fuel cells.
[0004] Studies have shown that the formation of a larger hydrophilic proton conductive phase region in the proton membrane is conducive to the improvement of the conductivity of the proton exchange membrane. The prior art compares the performance of polysulfone membranes with different graft chain lengths, branched and unbranched fluorinated alkyl sulfonic acid side chains. The stronger the acidity, the longer the graft chain, and the easier it is for the hydrophilic side chains with branched structures to aggregate to form a larger hydrophilic proton conductive phase region, and the proton conductivity of the prepared proton exchange membrane is higher. The prior art has disclosed an ABA-type block-based proton exchange membrane with polystyrene at both ends and sulfonated polyphenylene sulfide sulfone in the middle segment. With the increase in the volume fraction of the middle segment, the microphase separation structure of the proton exchange membrane undergoes a change from spheres to columns and then to layers. The proton conductivity of the membrane is significantly improved with the increase in the continuity of the hydrophilic phase region. Although the prior art can well improve the conductivity of the membrane material, the preparation process requirements for the membrane material are relatively high, the reaction conditions are relatively harsh, and the production cost is also high. Summary of the invention
[0005] The purpose of the present invention is to address the deficiencies of the prior art and to provide a high-conductivity proton exchange membrane and a preparation method thereof.
[0006] In a first aspect, a method for preparing a high conductivity proton exchange membrane comprises:
[0007] Step 1, placing a polymer material in an organic solvent, ultrasonicating until completely dissolved, and preparing a 1-10 wt% polymer solution; the polymer material contains bromomethyl or chloromethyl;
[0008] Step 2, adding a quaternizing agent to the polymer solution, and subjecting the solution to ultrasonic reaction at 30-80° C. for 5-180 min;
[0009] Step 3, adding a free radical inhibitor to the solution obtained in step 2, wherein the polymer material includes bromomethyl or chloromethyl; and stirring at room temperature for 10-120 min to obtain a casting solution;
[0010] Step 4: Pour the casting solution into an ultra-flat culture dish, put it into an oven, and bake the film at 45-80° C. for 24-60 hours to complete the preparation of the proton exchange membrane.
[0011] Preferably, in step 1, the polymer material is any one of brominated polyphenylene ether and poly(p-chloromethylstyrene-styrene).
[0012] Preferably, in step 1, the organic solvent is at least one of N-methylpyrrolidone, N,N-dimethylacetamide and N,N-dimethylformamide.
[0013] Preferably, in step 2, the quaternizing agent is triethylamine.
[0014] Preferably, in step 3, the free radical inhibitor is a phenolic reagent, a ketone reagent or an amine reagent, the phenolic reagent is 4-tert-butylphenol; the ketone reagent includes benzophenone; the amine reagent is N-phenyl-1-naphthylamine or diphenylamine sulfide.
[0015] In a second aspect, a high conductivity proton exchange membrane prepared by any method described in the first aspect is provided.
[0016] The beneficial effects of the present invention are:
[0017] 1. The present invention adopts the method of adding different types of free radical inhibitors to increase the acid absorption rate of the proton exchange membrane, thereby improving the continuity of the hydrophilic phase region in the proton exchange membrane material, and further achieving the effect of improving the conductivity of the proton exchange membrane material, providing a new path for improving the performance of the proton exchange membrane.
[0018] 2. The method for increasing the conductivity of the proton membrane by adding a free radical inhibitor provided by the present invention is simple and convenient to operate, has low requirements on instruments, and has a short reaction time.
[0019] 3. The free radical inhibitor material used in the present invention is low in price, rich in variety, small in dosage, and can effectively improve the conductivity of the proton exchange membrane. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 is a flow chart for preparing quaternary ammonium polyphenylene ether membrane materials;
[0021] Figure 2The conductivity of the proton membrane doped with different free radical inhibitors varies with temperature;
[0022] Figure 3 AFM images of proton exchange membranes doped and undoped with 4-tert-butylphenol. DETAILED DESCRIPTION
[0023] The present invention is further described below in conjunction with embodiments. The description of the following embodiments is only used to help understand the present invention. It should be noted that for ordinary persons in the art, without departing from the principle of the present invention, the present invention can also be modified in some ways, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
[0024] Embodiment 1:
[0025] In order to solve the problems of the prior art, Example 1 of the present application improves the continuity of the hydrophilic phase region in the proton exchange membrane material in a simple and low-cost manner, thereby improving the conductivity of the proton exchange membrane.
[0026] Specifically, a method for preparing a high conductivity proton exchange membrane comprises:
[0027] Weigh 1.5 g of brominated polyphenylene ether and add it to a mixed solution of 10 mL N-methylpyrrolidone (NMP) and 25 mL N, N-dimethylacetamide (DMAc), ultrasonicate until dissolved, then add 475 μL triethylamine, and ultrasonicate for 3 h at 30 ° C. The obtained solution was divided into five parts, one of which was free of substances, and the remaining four parts were added with four different free radical inhibitors to obtain five different casting solutions. Among them, the four different free radical inhibitors include: 4-tert-butylphenol (4-TBP), benzophenone (BP), N-phenyl-1-naphthylamine (PNA) and diphenylamine sulfide (PTZ). The amount of free radical inhibitor is 0.24 times the amount of bromomethyl substance in brominated polyphenylene ether (0.3 g). The five parts of casting solution were stirred at room temperature for 10 min at the same time, poured into an ultra-flat petri dish, and dried in an oven at 80 ° C for 48 h to obtain QPPO. 0.75 and QPPO 0.75 -R 0.24 Proton exchange membrane (where R represents the type of free radical inhibitor added). Figure 1 The flowchart of preparing the quaternized polyphenylene ether membrane material with 4-tert-butylphenol, benzophenone, N-phenyl-1-naphthylamine and diphenylamine sulfide as added ingredients is shown.
[0028] The methods for determining the acid absorption performance of proton exchange membranes include:
[0029] The prepared proton exchange membrane was cut into rectangles of a certain size and placed in an oven to dry to constant weight. Its mass was weighed with an electronic balance and recorded as m0 (g). The length (cm), width (cm), and thickness (cm) were measured. The membrane was soaked in an 85 wt% phosphoric acid aqueous solution and placed in an oven at a certain temperature for 24 h. The membrane material was taken out and quickly dried with filter paper. The mass of the membrane material was weighed and recorded as m e (g), and measure its length, width and thickness. The phosphoric acid doping level of the membrane can be calculated according to the following formula:
[0030]
[0031] If the area and volume of the dry film before absorbing phosphoric acid are recorded as A0 and V0 respectively, the area after absorbing phosphoric acid for 24 h is A0. e and V e , the area swelling ratio (AS) and volume swelling ratio (VS) of the membrane can be obtained by the following formula:
[0032]
[0033]
[0034] in, is the area swelling ratio, is the volume swelling ratio.
[0035] The specific analysis of the acid absorption performance and conductivity of the proton exchange membrane is as follows:
[0036] The acid absorption rate, area volume swelling rate and conductivity at 180°C of the prepared membrane material are shown in Table 1. As can be seen from the table, adding different types of free radical inhibitors to the proton exchange membrane will increase the acid absorption rate, area and volume swelling rate of the proton exchange membrane to varying degrees. Figure 2 The conductivity of the prepared membrane material changes with temperature. Figure 2 It can be seen that after doping with free radical inhibitors, the conductivity of the proton membrane increases to varying degrees. Among them, when 4-TBP is added, the conductivity of the proton membrane increases most significantly. At 180°C, the conductivity of the proton exchange membrane doped with free radical inhibitors is 2.2 times that of the proton membrane without free radical inhibitors. AFM characterization of the membrane material (such as Figure 3 As shown in the figure, it can be seen that the continuity of the hydrophilic phase region of the membrane material is significantly increased after doping with the free radical inhibitor. Figure 3 The membrane material corresponding to (a) is QPPO 0.75 , undoped 4-tert-butylphenol; Figure 3 The membrane material corresponding to (b) is QPPO 0.75 -4-TBP 0.12 ; Figure 3The membrane material corresponding to (c) is QPPO 0.75 -4-TBP 0.24 Among them, the membrane material QPPO x -4-TBP y Here, x represents that the amount of triethylamine in the reaction is x times the amount of bromomethyl in the brominated polyphenylene ether, and y represents that the amount of 4-TBP in the reaction is y times the amount of bromomethyl in the brominated polyphenylene ether.
[0037] Table 1 Changes in conductivity, acid absorption rate and swelling of proton exchange membranes doped with different types of free radical inhibitors
[0038]
[0039] Embodiment 2:
[0040] Based on Example 1, Example 2 of the present application provides another method for preparing a high conductivity proton exchange membrane, comprising:
[0041] Weigh 0.6 g of poly(p-chloromethylstyrene-styrene copolymer) and add it to a mixed solution of 4 mL of N-methylpyrrolidone (NMP) and 16 mL of N, N-dimethylacetamide (DMAc), ultrasonicate until dissolved, then add 2 mL of triethylamine, and ultrasonicate for 2 h at 60 °C. The obtained solution was divided into two parts, one of which was added with 4-tert-butylphenol, and the amount of the substance added was 1.5 times the amount of the chloromethyl substance in the poly(p-chloromethylstyrene-styrene copolymer), and the other part was not added with the substance as a blank control group. The two parts were stirred at room temperature for 30 min at the same time to obtain two different casting solutions, which were poured into an ultra-flat culture dish and baked in an oven at 60 °C for 48 h to obtain QP(VBC-St) and QP(VBC-St)-4-TBP proton exchange membranes.
[0042] The steps for determining the acid absorption performance of the proton exchange membrane can be referred to Example 1, and the present application will not repeat them here.
[0043] The acid absorption performance and conductivity of the proton exchange membrane are shown in Table 2.
[0044] Table 2 Acid absorption performance and conductivity of proton exchange membrane
[0045]
[0046] It can be seen from Table 2 that after the QP (VBC-St) proton exchange membrane was doped with the 4-TBP free radical inhibitor, the acid absorption rate, area and volume swelling rate, and conductivity at 180 °C of the membrane material increased significantly.
[0047] Embodiment 3:
[0048] Based on Example 1, Example 2 of the present application provides another method for preparing a high conductivity proton exchange membrane, comprising:
[0049] Weigh 0.6 g of brominated polyphenylene ether, add it to a mixed solution of 2 mL N-methylpyrrolidone (NMP) and 10 mL N, N-dimethylformamide (DMF), sonicate until dissolved, then add 90 mL of triethylamine, and sonicate for 2 h at 30°C. The obtained solution was divided into two parts, one of which was added with benzophenone, and the amount of the substance added was 1.5 times the amount of the bromomethyl substance in the brominated polyphenylene ether. The other part was not added with the substance as a blank control group. The two parts were stirred at room temperature for 10 min at the same time to obtain two different casting solutions, which were poured into an ultra-flat culture dish and dried in an oven at 70°C for 36 h to obtain QPPO. 0.7 and QPPO 0.7 -BP proton exchange membrane.
[0050] The steps for determining the acid absorption performance of the proton exchange membrane can be referred to Example 1, and the present application will not repeat them here.
[0051] The acid absorption performance and conductivity of the proton exchange membrane are shown in Table 3.
[0052] Table 3 Acid absorption performance and conductivity of proton exchange membrane
[0053]
[0054] Embodiment 4:
[0055] Based on Example 1, Example 4 of the present application provides another method for preparing a high conductivity proton exchange membrane, comprising:
[0056] Weigh 0.6 g of poly(p-chloromethylstyrene-styrene copolymer) and add it to 20 mL of N,N-dimethylacetamide (DMAc), ultrasonicate until dissolved, then add 1 mL of triethylamine, and ultrasonicate for 3 h at 80°C. The obtained solution was divided into two parts, one of which was added with benzophenone, and the amount of the substance added was 1.5 times the amount of the chloromethyl substance in the poly(p-chloromethylstyrene-styrene copolymer), and the other part was not added with the substance as a blank control group. The two parts were stirred at room temperature for 20 min at the same time to obtain two different casting solutions, which were poured into an ultra-flat culture dish and baked in an oven at 60°C for 48 h to obtain QP(VBC-St) and QP(VBC-St)-BP proton exchange membranes.
[0057] The steps for determining the acid absorption performance of the proton exchange membrane can be referred to Example 1, and the present application will not repeat them here.
[0058] The acid absorption performance and conductivity of the proton exchange membrane are shown in Table 4.
[0059] Table 4 Acid absorption performance and conductivity of proton exchange membrane
[0060]
[0061] From Table 4, we can see that QPPO 0.7 After the proton exchange membrane was doped with BP free radical inhibitor, the acid absorption rate, area and volume swelling rate, and conductivity at 180°C of the membrane material increased significantly.
[0062] Embodiment 5:
[0063] Based on Example 1, Example 5 of the present application provides another method for preparing a high conductivity proton exchange membrane, comprising:
[0064] According to the ratio of adding 0.6 g of brominated polyphenylene ether to a mixed solution of 4 mL of N-methylpyrrolidone (NMP) and 5 mL of N, N-dimethylacetamide (DMAc), ultrasonically dissolve it, and prepare 5 solutions respectively. Triethylamine (calculated as 0.6 g of brominated polyphenylene ether) with a content of 100%, 90%, 80%, 75% and 70% of the amount of bromomethyl substance in brominated polyphenylene ether is added to the 5 solutions respectively, and ultrasonically react at 60°C for 3 h. Each solution is divided into 2 parts, one of which is free of substance, and the other is added with 4-TBP. The amount of free radical inhibitor is 0.24 times the amount of bromomethyl substance in brominated polyphenylene ether (calculated as 0.3 g). The solutions are stirred at room temperature for 10 min at the same time to obtain ten different casting solutions, which are poured into ultra-flat culture dishes and baked in an oven at 80°C for 48 h to obtain QPPO1. 1.0 、QPPO1 1.0 -4-TBP 0.24 、QPPO 0.9 、QPPO 0.9 -4-TBP 0.24 、QPPO 0.8 、QPPO 0.8 -4-TBP 0.24 、QPPO 0.75 、QPPO 0.75 -4-TBP 0.24 、QPPO 0.7 、QPPO 0.7 -4-TBP 0.24 .
[0065] The steps for determining the acid absorption performance of the proton exchange membrane can be referred to Example 1, and the present application will not repeat them here.
[0066] The acid absorption performance and swelling performance of the proton exchange membrane are shown in Table 5.
[0067] Table 5 Changes in acid absorption and area volume swelling rate of QPPO membrane materials with different quaternization degrees before and after doping with the same amount of 4-tert-butylphenol
[0068]
[0069] The acid absorption rate and area volume swelling rate of the prepared membrane material are shown in Table 5. It can be seen from Table 5 that the acid absorption rate, area and volume swelling rate of the proton exchange membrane can be improved to varying degrees after adding 4-TBP to the proton exchange membrane. Among them, for the proton exchange membrane with a high degree of quaternization, the addition of 4-TBP can significantly improve the conductivity.
Claims
1. A method for preparing a high conductivity proton exchange membrane, characterized in that: include: Step 1, placing a polymer material in an organic solvent, ultrasonicating until completely dissolved, and preparing a 1-10 wt% polymer solution; the polymer material contains bromomethyl or chloromethyl; Step 2, adding a quaternizing agent to the polymer solution, and subjecting the solution to ultrasonic reaction at 30-80° C. for 5-180 min; Step 3, adding a free radical inhibitor to the solution obtained in step 2, wherein the amount of the free radical inhibitor is 0.24-1.5 times the amount of the bromomethyl or chloromethyl substance in the polymer material, and stirring at room temperature for 10-120 min to obtain a casting solution; Step 4: Pour the casting solution into an ultra-flat culture dish, put it into an oven, and bake the film at 45-80° C. for 24-60 h to complete the preparation of the proton exchange membrane.
2. The method for preparing a high conductivity proton exchange membrane according to claim 1, characterized in that: In step 1, the polymer material is any one of brominated polyphenylene ether and poly(p-chloromethylstyrene)-styrene.
3. The method for preparing a high conductivity proton exchange membrane according to claim 2, characterized in that: In step 1, the organic solvent is at least one of N-methylpyrrolidone, N,N-dimethylacetamide and N,N-dimethylformamide.
4. The method for preparing a high conductivity proton exchange membrane according to claim 3, characterized in that: In step 2, the quaternizing agent is triethylamine.
5. The method for preparing a high conductivity proton exchange membrane according to claim 4, characterized in that: In step 3, the free radical inhibitor is a phenolic reagent, a ketone reagent or an amine reagent, the phenolic reagent is 4-tert-butylphenol; the ketone reagent includes benzophenone; the amine reagent is N-phenyl-1-naphthylamine or diphenylamine sulfide.
6. A high conductivity proton exchange membrane prepared by the method of claim 1.
Citation Information
Patent Citations
High-oxidization-resistance and high-conductivity crosslinked type polybenzimidazole high-temperature proton exchange membrane and preparation method therefor
CN106549171A
Method for improving alkali-resisting stability of cationic polymer
CN107513167A
Antioxidant proton exchange membrane, preparation method thereof and proton exchange membrane fuel cell
CN115084608A
Proton exchange membrane and catalyst-coated proton exchange membrane
US20240426009A1